Morphological and histochemical demonstration of hooks in the rostellar region of Cysticercus bovis - Zdárská, Z (Folia parasitologica, 1976)
Hooklets and early developmental stages of hooks were discovered in the tegument among the microtriches in the rostellar region of 83- and 108-day-old Cysticercus bovis. The cortical layer of hooks consists of proteins with tyrosine and SS groups. The rostellar sac and bulb are distinctly developed in the parenchyma of the rostellar region.
Keywords: histocytochemie; skot; Animals; Cattle; cysticercus; Histocytochemistry; Cysticercus; zvířata; Taenia